2019
DOI: 10.1039/c9cp00612e
|View full text |Cite
|
Sign up to set email alerts
|

What are the effects of the serine triad on proton conduction of an influenza B M2 channel? An investigation by molecular dynamics simulations

Abstract: A novel viewpoint about the effects of serine triad on proton conduction in a BM2 channel was proposed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 50 publications
1
15
0
Order By: Relevance
“…The probability density distributions of the conformation divided the curves into two populations with the relative weight shifting (Figure A): one is centered at 2.4–2.7 Å, representing the closed state, and the other has a wider distribution centered at 5.2–6.2 Å, adopting the open state. Interestingly, whether in negatively charged membrane or neutral membrane, the BM2 channel remained the closed state in His19 4 0 and adopted the open state in His19 4 4+ , consistent with our previous work. , Increase in RMSD is similar: 12% (from 2.4 to 2.7 Å) in His19 4 0 and 20% (from 5.2 to 6.2 Å) in His19 4 4+ . Compared to the neutral membrane, RMSD increased more in negatively charged membrane (Figure A), especially in the full-cationic state His19 4 4+ .…”
Section: Results and Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…The probability density distributions of the conformation divided the curves into two populations with the relative weight shifting (Figure A): one is centered at 2.4–2.7 Å, representing the closed state, and the other has a wider distribution centered at 5.2–6.2 Å, adopting the open state. Interestingly, whether in negatively charged membrane or neutral membrane, the BM2 channel remained the closed state in His19 4 0 and adopted the open state in His19 4 4+ , consistent with our previous work. , Increase in RMSD is similar: 12% (from 2.4 to 2.7 Å) in His19 4 0 and 20% (from 5.2 to 6.2 Å) in His19 4 4+ . Compared to the neutral membrane, RMSD increased more in negatively charged membrane (Figure A), especially in the full-cationic state His19 4 4+ .…”
Section: Results and Discussionsupporting
confidence: 91%
“…Experimental and theoretical investigations elucidated that hydration in the pore plays an important role in the proton conduction process. ,,,,,, Proton conduction at a low pH is facilitated by an expanded channel width and increased hydration. ,, Our previous work demonstrated that the widely open channel of BM2 (His19 4 4+ ) could allow more water molecules to enter the channel and form the complete water wire, and then strengthen channel hydration. As mentioned above, a negatively charged membrane facilitates expanding channel.…”
Section: Results and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…AM2 and BM2 are responsible for acid-activating the channel and transferring protons. , Therefore, M2 channel is an ideal target for anti-influenza drug design. In our previous work, we have shed light on the unique acid activation-promotion mechanism of the BM2 channel and determined the key factors of affecting acid-activation and transferring protons. Amantadine (1-adamantanamine hydrochloride, referred to as AMT in this work) is best known to inhibit AM2 channel favoring the down binding mode (Figure ) by binding and blocking the channel pore and impeding proton transport through the pore. However, there is no effective inhibitor or drug against BM2 channel. AMT lacks inhibitory activity against BM2 channel, which has a highly conserved functional motif common to the AM2 channel .…”
mentioning
confidence: 99%